- 1-800-665-6601
- info@tutorpace.com

Solution: Given here is the quadratic equation x

The first step is to solve for the quadratic equation.

The equation can be written as x

Now factoring the common terms gives x(x + 3) + 3(x + 3) = 0.

Hence (x + 3) (x + 3) = 0

Therefor x = 3 is the solution.

Solution: Given here is the quadratic equation x

The first step is to solve for the quadratic equation.

The equation can be written as x

Now factoring the common terms gives x(x + 2) + 5(x + 2) = 0.

Hence (x + 5) (x + 2) = 0

Therefor x = -5, - 2 are the solutions.